Structure Activity Relationship Studies of Some Potent Antifungal Flavones, 4-Thioflavones and 4-Iminoflavones - Hasan, Aurangzeb; Mughal, E.U.; Sadiq, A. (Asian Journal of Chemistry, 2012)
A series of flavones, carrying halogens, methoxy and nitro groups at various positions were synthesized by the Baker-Venkataraman rearrangement and were subsequently converted to 4-thioflavones and 4-iminoflavones. The synthesized compounds were evaluated for their in vitro antifungal activity against Trichophyton longifusus, Candida albicans, Aspergillus flavus, Microsporum canis, Fusarium solani and Candida glabrata. All synthesized compounds showed significant activity against T. longusus, A. flavus, M. canis and F. Solani but inactive against C. albicans and C. glabrata, respectively. 2-phenyl-4H-1-benzopyran-4-thiones were relatively more active than flavones and 4-iminoflavones. However, some compounds were even more active than standard miconazol and amphotericin B drugs.